Flozins in Reducing Cardiovascular and Metabolic Risk: A Literature Review - Daria Sieniawska; Julia Sieniawska; Patrycja Proszowska (Nicolaus Copernicus University in Toruń, 2024)
Introduction Cardiovascular diseases (CVD) are a significant worldwide health issue, impacting millions of patients and being the primary cause of global illness and death. The combination of SGLT2 inhibitors with weight loss and physical activity can significantly reduce cardiovascular risk. Beyond their primary antihyperglycemic effects, SGLT2 inhibitors elicit pleiotropic benefits including weight loss and favorable alterations in lipid metabolism, culminating in a cardioprotective metabolic environment. Aim of the study The aim of the study is to investigate the pleiotropic benefits of SGLT2 inhibitors, including their effects on weight loss, lipid metabolism, and cardiovascular health, in individuals. Materials and methods This study presents the current state of knowledge about metabolic and cardiovascular benefits associated with SGLT2 inhibitors in various scientific articles. PubMed database was searched for articles written in English. The search included the keywords "SGLT2-inhibitors"; "SGLT2-inhibitors mechanism of action"; "heart failure"; "cardiovascular events". Results SGLT2 inhibitors enhance glycemic control, decrease body weight and visceral fat, and ameliorate several metabolic abnormalities linked to metabolic syndrome, including lipid profile. Clinical investigations have underscored the cardiovascular benefits conferred by SGLT2 inhibitors. Reductions in major adverse cardiovascular events and heart failure-related hospitalizations have been consistently observed, irrespective of diabetic status. Guidelines now advocate for the incorporation of SGLT2 inhibitors as first-line therapies for HFrEF and HFpEF. This endorsement underscores the transformative impact of SGLT2 inhibitors on cardiovascular outcomes.